Low-Dose, Prophylactic, Extended-Field, Intensity-Modulated Radiotherapy Plus Concurrent Weekly Cisplatin for Patients With Stage IB2-IIIB Cervical Cancer, Positive Pelvic Lymph Nodes, and Negative Para-aortic Lymph Nodes. Issue 5 (1st June 2014) - Liang, Ji-An; Chen, Shang-Wen; Hung, Yao-Ching; Yeh, Lian-Shung; Chang, Wei-Chun; Lin, Wu-Chou; Chang, Yin-Yi
Abstract : Objective: The objective of this study was to assess prospectively the clinical outcomes of low-dose prophylactic extended-field, intensity-modulated radiotherapy (IMRT) plus concurrent weekly cisplatin for patients with stage IB2-IIIB cervical cancer, positive pelvic lymph nodes (PLNs), and negative para-aortic lymph nodes (PALNs). Methods: Thirty-two patients with stage IB2-IIIB cervical cancer with positive PLN and negative PALN were included prospectively. All lymph nodes were assessed with positron emission tomography. The PALN field, including lymphatics from the superior border of L1 to the L4-L5 interphase, was irradiated concurrently with pelvic IMRT with a prescribed dose of 40 Gy in 25 fractions. Chemotherapy consisted of cisplatin delivered weekly at a dose of 40 mg/m 2 . Using historical controls treated with pelvic radiotherapy, the survival curves were compared to assess the difference between the 2 treatment periods. Results: Thirty-one patients completed the allocated extended-field IMRT, and all finished the planned pelvic IMRT and brachytherapy. Acute ≥ grade 3 gastrointestinal, genitourinary, and hematologic toxicities were seen in 2, 1, and 18 patients, respectively. During a median follow-up of 33 months, 5 patients developed out-field distant recurrences. One patient had a late grade 3 gastrointestinal complication, and 1 patient had genitourinary toxicity. The 3-year actuarial overall survival, disease-free survival, and distant metastasis–free survival for the study cohort and historic controls were 87% versus 62% ( P = 0.02), 82% versus 54% ( P = 0.02), and 79% versus 57% ( P = 0.01), respectively. Conclusions: Extended-field IMRT of 40 Gy to the PALN plus concurrent cisplatin can effectively eradicate subclinical disease at the PALN and improve the outcome for patients with PLN-positive stage IB2-IIIB cervical cancer.